2017
DOI: 10.2174/1573397112666160404124532
|View full text |Cite
|
Sign up to set email alerts
|

Probing The Relation Between Vitamin D Deficiency and Progression of Medial Femoro-tibial Osteoarthitis of the Knee

Abstract: 25 (OH) D levels were significantly decreased in knee OA patients. Significant deterioration of the medial menisci was observed in OA patients with 25 (OH)D levels <10 ng/ml suggesting that Vit D deficiency may play a role in the progression of medial femoro-tibial OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…The present study revealed significant decrease in the levels of Vitamin D in study subjects (p<0.05). Our results were corroborated with Bassiouni et al (15) ,Veronese et al (16) and Jansen and Haddad (17) found that serum 25(OH)D levels were significantly decreased in the patients with knee OA and noted that medial meniscal deterioration was seen in patients with low vitamin D levels.…”
Section: Discussion:-supporting
confidence: 91%
“…The present study revealed significant decrease in the levels of Vitamin D in study subjects (p<0.05). Our results were corroborated with Bassiouni et al (15) ,Veronese et al (16) and Jansen and Haddad (17) found that serum 25(OH)D levels were significantly decreased in the patients with knee OA and noted that medial meniscal deterioration was seen in patients with low vitamin D levels.…”
Section: Discussion:-supporting
confidence: 91%
“…Vitamin D reduced pain and improved function in knee OA patients. While deficiency in endogenous vitamin D, reflected by low levels of circulating 25 OH vitamin D, was associated with the onset and progression of knee OA [38], maybe through an increased frequency of medial meniscus lesions [39], results of individual RCTs were inconclusive [40][41][42][43]. Their outcomes varied from a non-significant trend for symptom reduction [40][41][42] to a small but statistically significant benefit on pain and function after 12 months of administration [43].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that patients with OA have decreased vitamin D serum levels ( Table 2 ). Bassiouni et al 9 and Veronese et al 49 both found that serum 25(OH)D levels were significantly decreased in the patients with knee OA and noted that medial meniscal deterioration was seen in patients with low vitamin D levels. In a cross-sectional study, Jansen and Haddad 24 showed that in elderly patients with advanced knee OA, there was a high prevalence of vitamin D deficiency.…”
Section: Vitamin D and Osteoarthritismentioning
confidence: 99%